The Nutrient Content of Eco-enzymes from Mixture of Various Fruit Peels - Siregar, Benedicta Lamria; Siallagan, Rexi Sebastian; Butar Butar, Suwarnita; Mahmudi, Bambang; Pujiastuti, Elisabeth Sri (Universitas Panji Sakti, 2024)
Today, many institutions and individuals are paying attention to the development of technologies used in sustainable agriculture. One of the technologies is eco-enzyme that can be used as organic fertilizer. Several researchers have studied the use of eco-enzymes in agriculture, but studies on the nutrient content of eco-enzymes are still very limited. This research was conducted to investigate the nutrient content of two eco-enzyme preparations. The eco-enzymes were produced through the fermentation process of water, fruit peels, and molasses with a weight ratio of 10 : 3 : 1. Fruit peels used for Eco-enzyme A were banana, melon, watermelon, orange, and pineapple peels, while for Eco-enzyme B were banana, mango, watermelon, orange, and pineapple peels. The fermentation period for Eco-enzyme A was seven months, while for Eco-enzyme B was eight months. The results of the analysis showed that the two eco-enzymes contained various nutrients, both macro (C, N, P, K, Mg, Ca) and micro (Mn, Zn, B, Fe, Cu) ones, that were consistently higher in Eco-enzyme A. Both eco-enzymes were acidic, where the pH of Eco-enzyme A and B were 3.95 and 3.50, respectively. The data obtained were expected to be a basic reference for further research on eco-enzymes.